MO091: Serum Hepatocyte Growth Factor is Associated With Albuminuria in Subjects With Optimal Blood Pressure and Untreated Arterial Hypertension. (3rd May 2022) - Fistrek Prlic, Margareta; Knezevic, Tamara; Ivkovic, Vanja; Fucek, Mirjana; Abramovic Baric, Mirta; Brzic, Ivan; Domislovic, Marija; Jelakovic, Bojan
Abstract: BACKGROUND AND AIMS: Hepatocyte growth factor (HGF) is a pleiotropic factor that has a protective role in acute renal injury. HGF prevents the development of chronic renal fibrosis in animal models via inhibition of transforming growth factor β1 expression and consequently reduces podocyte injury and proteinuria.[1, 2 ] Serum HGF concentration is associated with systolic arterial blood pressure (BP) and is higher in hypertensive than in normotensive individuals, especially if complications of arterial hypertension are developed.[3, 4 ] Our aim was to determine the association of serum HGF concentration and albuminuria in normotensive subjects and subjects with untreated arterial hypertension. METHOD: Data from 563 subjects (57.8% women, mean age 48 years) was analyzed. After clinical examination, fasting blood and urine samples were drawn. Albuminuria was normalized to urine creatinine and expressed as an albumin/creatinine ratio (ACR). HGF was measured using a commercial test. BP was measured according to ESH guidelines. Based on BP values, subjects were divided into two groups: OBP: subjects with optimal blood pressure (BP < 120/80 mmHg, N = 295), and UAH: subjects with untreated arterial hypertension (BP > 140/90 mmHg, N = 268). RESULTS: Subjects with UAH were significantly older and had higher values of body mass index, waist circumference, serum total, and LDL-cholesterol levels, triglyceride levels, fasting glucose levels, and ACR (all P < 0.001). Serum HGF concentrations were also higher in UAH subjects, but the difference was not significant (270.8 versus 304.2 pg/mL, P = 0.651). Subjects with ACR > 30 mg/g had higher values of serum HGF concentration in comparison with subject with ACR < 30 mg/g in both groups, but the difference again was not significant (262.1 versus 527.8 pg/ml, P = 0.747 and 328.6 versus 843.5 pg/ml, P = 0.066, respectively). Serum HGF concentration showed a significant positive correlation to ACR in both groups (P < 0.05). Multivariate regression analysis showed that BP was an independent predictor of ACR increase (Beta = 0.134, P = 0.028), whereas age, sex and serum glucose were not. Serum HGF concentration was also a strong predictor of the ACR increase (Beta = 0.376, P < 0.001). CONCLUSION: Serum HGF concentration is associated with ACR in subjects with not only untreated arterial hypertension but also optimal blood pressure. We found that HGF is an independent predictor of the ACR increase in this population.